Reforming Youthful Offenders: The Case of Diepkloof Reformatory School, 1935-1948 (Historia, 2025)
This article explores Alan Paton’s efforts towards turning a prison into a school, the task which he was given by the Union Education Department following numerous debates in parliament in 1934. The aim was to transfer all reformatory institutions for juveniles run by the Department of Prisons, to the Union Education Department. Equally important, this article focuses on Paton’s journey and experiences as the principal of Diepkloof Reformatory School from 1935 to 1948. The focus is on African juvenile offenders since Diepkloof Reformatory was the only reformatory for African boys in the Union and the continent of Africa until the 1960s. The account delves into the day-to-day lives of pupils who were sent to the Reformatory School by the Children’s Courts. Paton, driven by a vision of rehabilitation over punishment, introduced reforms emphasising education, skills training, and self-discipline. The article explores the day-to-day lives of the youth incarcerated at Diepkloof Reformatory, an angle that has received limited attention from historians and reformists. It also extends beyond the reformatory, addressing the release conditions, home suitability, and the struggles some boys experienced in reintegrating into society. Paton's vision to make Diepkloof a place of justice and opportunity faced setbacks, yet his influence left a lasting impact on others who found success after rehabilitation. The article studies primary sources and correspondence to provide an understanding of the rehabilitation efforts Paton made to turn this prison into a school and the recommendations made by the Board of Management towards smooth administration to ensure an effective rehabilitation process for the boys.
Keywords: Diepkloof Reformatory School; juvenile delinquency; youth; pupils; Africans; urban areas